Tìm x :
x - 23 = 45
x + 23 = 45
Tìm x
a) x + 1 2 = − 4 5
b) − 3 4 − x = 2 3
c) 2 3 5 + − 3 5 : x = − 2 3
a ) x = − 4 5 − 1 2 ⇔ x = − 13 10 b ) x = − 3 4 − 2 3 ⇔ x = − 17 12 c ) − 3 5 : x = − 2 3 − 2 3 5 ⇔ − 3 5 : x = − 49 15 ⇔ x = − 3 5 : − 49 15 ⇔ x = 9 49
?????????????????????/??///??//???/
1) Tìm x :
x + 125 - 45 + ( 12 + 23 ) = 155
x * 12 = ( 45 + 45 )
a) x + 125 - 45 + (12+23) = 40
=> x + 125 - 45 + 35 = 40
=> x + 115 = 40
=> x = 40 - 115
=> x = -75
b) x * 12 = (45 + 45)
=> x * 12 = 90
=> x = 90 : 12
=> x = 7,5
x + 125 - 45 + ( 12 + 23 ) = 40
=> x + 125 +( -45) + 35 = 40
=> x + 80 +35 = 40
=> x + 115 = 40
=> x = -75
x * 12 = ( 45 + 45 )
=> x * 12 = 90
=> x = 90 : 12
=> x = 15/2 = 7.5
a) x + 125 - 45 + (12 + 23) = 40
x + 125 - 45 + 35 = 40
x = 40 - 35 + 45 - 125
x = - 65
b) x * 12 = 45 + 45
x * 12 = 90
x = 90 : 12
x = 7,5
Tính :
45 x 32 + 45 x 23
45 : 32 + 45 : 23
43 x 33 + 43 x 22 + 43
45 x 32 + 45 x 23
= 45 x ( 32 + 23 )
= 45 x 55
= 2475
45 : 32 + 45 : 23
= 1,40625 + 1,9566521739
= 3,362771739
43 x 33 + 43 x 22 + 43
= 43 x ( 33 + 22 + 1 )
= 43 x 56
= 2408
45 x 32 + 45 x 23
= 45 x ( 32 + 23 )
= 45 x 55
= 2475
45 : 32 + 45 : 23
= 1,40625 + 1,9566521739
= 3,362771739
43 x 33 + 43 x 22 + 43
= 43 x ( 33 + 22 + 1 )
= 43 x 56
= 2408
45 x 32 + 45 x 23
= 45 x ( 32 + 23 )
= 45 x 55
= 2475
45 : 32 + 45 : 23
= 1,40625 + 1,9566521739
= 3,362771739
43 x 33 + 43 x 22 + 43
= 43 x ( 33 + 22 + 1 )
= 43
k mk nha mai đổi tk bn tk mk câu này
Tìm x, biết:
a ) 4 7 . x + 2 3 = − 1 5 b ) 2 9 − 7 8 . x = 1 c ) 4 5 + 7 6 : x = 1 6 d ) 5 7 : x − 1 = 2 3
Tìm x :
x + 22 = 45
x - 45 = 23
x + 22 = 45 x - 45 = 23
x = 45 - 22 x = 45 + 23
x = 23 x = 68
x + 22 = 45
x = 45 - 22
x = 23
x - 45 = 23
x = 23 + 45
x = 68
x + 22 = 45
x = 45 - 22
x = 23
x - 45 = 23
x = 23 + 45
x = 68
Tìm x, biết:
a ) 4 7 . x + 2 3 = − 1 5 b ) 2 9 − 7 8 . x = 1 ; c ) 4 5 + 7 6 : x = 1 6 d ) 5 7 : x − 1 = 2 3
a ) x = − 91 60 . b ) x = − 8 9 . c ) x = 35 19 . d ) x = 3 7 .
Tìm x biết 3 2 × 4 5 : x = 2 3
A. x= 6 5
B. x= 9 5
C. x= 8 5
D. x= 5 9
Đáp án B
Ta có : 3 2 . 4 5 : x = 2 3
6 5 : x = 2 3 x = 6 5 : 2 3 x = 6 5 × 3 2 x = 9 5
Đáp án cần chọn là: B
Tìm x biết x + 2 3 = − 1 12 . − 4 5
A. − 5 3
B. − 3 5
C. − 1 3
D. − 1 5
Đáp án cần chọn là: B
x + 2 3 = − 1 12 . − 4 5 x + 2 3 = 1 15 x = − 2 3 + 1 15 x = − 3 5
tìm x
32 + x = 45
45 -x = 23
66 - x + 3 = 41
32+x=45
x=45-32
x=13
45-x=23
x=45-23
x=22
66-x+3=41
66-x+3=41-3
66-x =38
x =66-38
x =28
32 + x = 45
x = 45 - 32
x = 13
45 - x = 23
x = 45 - 23
x = 22
66 - x + 3 = 41
66 - x = 38
x = 66 - 38
x = 28
32 + x = 45
x = 45 - 32
x = 13
45 - x = 23
x = 45 - 23
x = 22
66 - x + 3 = 41
x + 3 = 66 - 41
x + 3 = 25
x = 25 - 3
x = 22